A multiple sclerosis lifestyle behavior online course: Qualitative analysis of participants' motivations, expectations and experiences - Sandra L. Neate; William Bevens; Pia L. Jelinek; Kathleen M. Gray; T. J. Weiland; Nupur Nag; Steve Simpson-Yap; Steve Simpson-Yap; George A. Jelinek; M. Yu; Jeanette C. Reece (Frontiers Media S.A., 2022)
BackgroundModification of lifestyle-related risk factors for multiple sclerosis (MS) has been associated with improved health outcomes when compared with standard medical management alone. Based on an existing lifestyle modification program offered as a residential workshop, the MS Online Course (MSOC) was developed to translate the workshop into an online intervention. We performed a pilot randomized controlled trial (RCT), to assess the feasibility concepts of accessibility, learnability and desirability through quantitative and qualitative analyzes. In the present study, we performed additional qualitative analyzes to explore participants' motivations, expectations, and experiences of the MSOC. This study aims to complement prior feasibility analyzes and inform recruitment strategies and course content redevelopment so that its effectiveness may be assessed by examining behavior change and health outcomes in a future larger RCT.MethodsParticipants were recruited via online advertisements and randomized to either: the standard care course, containing material sourced from public facing MS websites; or the intervention course, based on an evidence-based lifestyle modification program for people with MS. Course completers were invited to participate in semi-structured interviews. Within a qualitative paradigm, reflexive thematic analysis of interviews was undertaken.ResultsOf 31 eligible participants, 17 completed the MSOC and 14 agreed to be interviewed. Four themes were identified in this analysis: (1) "Wanting to help others" (helping through volunteering, contributing to knowledge base, spreading the word; (2) "Seeking knowledge" (confirmation of existing knowledge; obtaining new knowledge, relevant, credible information); (3) "Doing what I can to help myself" (understanding lifestyle modification, changing my lifestyle, remaining well); and (4) "Changing attitudes" (finding positivity, feeling more confident and in control).ConclusionsParticipants were motivated to help others through research, help themselves by improving knowledge and to find ways to better manage their MS. Expectations included obtaining credible, reliable information, to substantiate existing knowledge, and to further understand lifestyle modification. Participants' experiences included confirmation of and obtaining new knowledge, and early implementation of modified lifestyle behaviors. These insights surrounding participants' motivations, expectations and experiences will assist in recruitment strategies, course redevelopment and outcome measures for the future RCT to examine the effectiveness of the MSOC.